The Impact of Migration on Rural Poverty: The Case Study of District Faisalabad, Pakistan - Kousar, Rakhshanda; Naz, Farah; Sadaf, Tahira; Adil, Sultan Ali; Shahid, Tayyab Zeeshan; Mushtaq, Shahid (International Journal of Economics and Financial Issues, 2016)
Internal-migration is the process of displacement of people within a country, mostly for better employment. Pakistan is among those South-Asian countries who have high rate of internal-migration. Poverty is considered to be an important factor in this context. This study estimates the rural-household poverty in Pakistan’s Faisalabad District and the impact of internal-migration on rural-household poverty. By using stratified random sampling technique, 180 respondents were selected and interviewed. Propensity Score Matching method was used to examine the causal effect of internal-migration on household-poverty level. Results reveal that the ATT estimates of 0.18 for poverty reduction which shows that the household participation in the internal-migration decreases the probability of poverty by 0.18 points, suggesting that internal-migration has a significant impact on poverty reduction among the rural-households. The study suggests the policy makers to focus on rural development and enhance labor productivity, so that internal-migration is discouraged, which will ultimately reduce poverty. Keywords: Internal-Migration, Rural-Poverty, Pakistan JEL Classifications: I320, J11, D310, D12